A retrospective cohort study to examine factors affecting live birth after hysteroscopic treatment of intrauterine adhesions - Zhao, Yuting; Huang, Xiaowu; Huang, Rui; Xu, Ruonan; Xia, Enlan; Li, Tin Chiu (Fertility and sterility, 2024)
To evaluate independent factors that affect the chance of live birth (LB) after hysteroscopic adhesiolysis in patients with intrauterine adhesions. Retrospective cohort study. Hysteroscopic center of Fuxing Hospital in Beijing, China. Patients diagnosed with Asherman syndrome between June 2020, and February 2022. Hysteroscopic adhesiolysis is followed by a second look hysteroscopy to assess the outcome and follow-up for a year. Live birth rate (LBR) without the use of assisted reproductive technologies at 12-month follow-up. Of the 544 women included in the cohort, the pregnancy rate at the end of 1 year of follow-up was 47.6% (95% confidence interval [CI] 45.5%–49.7%), and the LBR was 41.0% (95% CI 38.9%–43.1%). Stepwise multiple logistic regression analysis identified three independent predictors of LB in decreasing order of significance: increase in menstrual flow after surgery (odds ratio [OR] 3.69, 95% CI 1.77–8.21), postoperative endometrial thickness in the midluteal phase (OR 1.53, 95% CI 1.31–1.80), and the severity of recurred adhesion at second-look hysteroscopy (OR 0.62, 95% CI 0.50–0.76). Among subjects with good independent prognostic factors, namely, increased menstrual flow after surgery, postoperative endometrial thickness in the midluteal phase >6 mm, and no or minimal recurrence of adhesions at second-look hysteroscopy, the LBR was 69.0% (95% CI 65.4%–72.6%). On the other hand, in women (n = 26) without any of the three good prognostic factors, none had a successful LB (0). Overall, the LBR after treatment for Asherman syndrome was 41.0%. The prognosis is dependent on three outcome measures after surgery, namely, improvement in menstrual flow, postoperative endometrial thickness, and the minimal degree of recurrent adhesions at second-look hysteroscopy. Estudio retrospectivo de cohorte para evaluar los factores que afectan los nacimientos vivos después del tratamiento histeroscópico de las adherencias intrauterinas Evaluar los factores independientes que afectan la probabilidad de nacido vivo (NV) después de la adhesiólisis histeroscópica en pacientes con adherencias intrauterinas. Estudio retrospectivo de cohorte. Centro histeroscópico del Hospital Fuxing en Pekín, China. Pacientes diagnosticados con síndrome de Asherman entre Junio 2020, y Febrero 2022. La adhesiólisis histeroscópica es seguida de una histeroscopia de segunda mirada para evaluar el resultado y el seguimiento durante un año. Tasa de nacido vivo (TNV) sin el uso de tecnologías de reproducción asistida a los 12 meses de seguimiento. De las 544 mujeres incluidas en la cohorte, la tasa de embarazo al final de 1 año de seguimiento fue del 47.6 % (intervalo de confianza [IC] del 95 %: 45.5%–49.7 %), y la TNV fue del 41.0 % (IC del 95 %: 38.9%–43.1 %). El análisis de regresión logística múltiple por pasos identificó tres factores predictivos independientes de NV en orden decreciente de significancia: aumento del flujo menstrual después de la cirugía (odds ratio [OR] 3.69, IC del 95%: 1.77-8.21), grosor endometrial postoperatorio en la fase lútea media (OR 1.53; IC del 95%: 1.31-1.80) y la severidad de adherencias recurrentes en la histeroscopia de segunda mirada (OR 0.62; IC del 95%: 0.50-0.76). Entre los sujetos con buenos factores pronósticos independientes, es decir, aumento del flujo menstrual después de la cirugía, grosor endometrial postoperatorio en la fase lútea media >6 mm y ninguna o mínima recurrencia de adherencias en la histeroscopia de segunda mirada, la TNV fue del 69.0 % (IC del 95 %: 65.4%-72.6 %). Por otro lado, en las mujeres (n = 26) sin alguno de los tres factores de buen pronóstico, ninguna tuvo un NV exitoso (0). En general, la TNV tras el tratamiento del síndrome de Asherman fue del 41.0%. El pronóstico depende de tres medidas de resultado después de la cirugía, es decir, la mejoría en el flujo menstrual, el grosor endometrial postoperatorio y un grado mínimo de adherencias recurrentes en la histeroscopia de segunda mirada.